Germinação de sementes e otimização de técnicas de micropropagação de umbuzeiro (spondias tuberosa, arr.) anacardiaceae - Lima, Simone Cassiano de (2009)
The brazilian-plum (Spondias tuberosa, His) is a tropical fruit tree that has been consolidated in the market for agribusiness processing, due to its characteristic flavor of fruit. Accordingly, studies to optimize the propagation of plants are necessary for production of seedlings with agronomic and quality assurance measures. This study aimed at determining the efficient techniques for uniform seed germination, as brazilian-plum seed present mechanical dormancy, and establish optimal culture media for multiplication of shoots from the in vitro micropropagation. Firstly, in a greenhouse at the Universidade Federal do Rio Grande do Norte, was evaluated the influence of different methods of breaking dormancy in the emergence of seedlings of brazilian-plum and speed of germination (IVG) of seeds. After 60 days of cultivation, it was found that splay in the distal portion of the seed was the best treatment, with rates of 85.33% in germinability and 3.415 of IVG, compared with the treatment of seed-soaking in water for 12h + humus and the control group. Subsequently, new sources of seedling explants were obtained in studies of tissue culture. Laboratory of Plant Biotechnology that the university, was used stem apex, nodal segments and internodes in search of decontamination with various concentrations of calcium hypochlorite [Ca(OCl)2] and micropropagation, inoculating them in half WPM (1980) with various concentrations of 6-benzylaminopurine (BAP). We used 10 sample units with three replications for different concentrations of [Ca(OCl)2], BAP and explants type. After thirty days, which was observed for the control of contamination, during the establishment in vitro, concentrations of [Ca(OCl)2] between 0.5% and 2.0% were effective in combating exogenous contamination of the apex. In nodal segments and internodes, concentrations of [Ca(OCl)2] between 1.0% and 2.0% and 1.5% and 2.0% were respectively, sufficient to reduce the percentage of losses in these infestations explants. For micropropagation, the culture medium supplemented with 0.1 mg.L-1 BAP promotes better development of multiple shoots per explants from nodal segment. However, success does not get to shoot training in internodal segment